Helping Surrogate Decision-Makers Through Difficult Conversations - Nortjé, Nico (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2018)
Difficult conversations in the ICU are often seen as ones of getting a surrogate decision-maker to make an end-of-life decision. However, allowing the surrogate decision-maker to become a narrator can alleviate the daunting task lying ahead.